Home Advantage Perceptions in Elite Handball: A Comparison Among Fans, Athletes, Coaches, and Officials - Gershgoren, Lael; Levental, Orr; Basevitch, Itay (Frontiers in Psychology, 2022)
Home advantage in sports has been extensively researched in the academic literature over the past five decades (Jamieson, 2010). A review of the literature reveals several factors that consistently underly this phenomenon. One of the most documented is the home crowd effect. While the fans' effect on the results has been widely researched considering noise, size, and density, there are conflicting findings of the effect and its extent. Furthermore, the perceptions of fans, athletes, coaches, and officials of the causes of home advantage in general and the crowd effect in particular, remain marginal. This is especially important in the face of significant regulation changes in the stands caused by the COVID-19 pandemic. The current study, therefore, examined the perceptions of fans, athletes, coaches, and officials of the Israeli handball premier league regarding fans' contribution to the home advantage phenomenon along with the other factors (e.g., travel, officiating). A questionnaire examining perceptions regarding home advantage was distributed to 232 Israeli participants (117 fans, 59 players, 26 coaches, and 30 officials). Preliminary results, based on MANOVA, ANOVA, and post-hoc analyses, indicate significant differences in participants' perceptions of the different factors in general and the crowd in particular. Overall, the crowd was perceived as the most important factor contributing to the home advantage phenomenon (M=5.7). Furthermore, fans perceived their contribution (i.e, the crowd) significantly higher than the rest of participants (p=.001; i.e., players, coaches and officials). On the other hand, officials ranked their contribution to the home advantage effect as low and significantly under ranked their contribution in comparison to the other groups (p<.001). This result suggests that officials perceive themselves as relatively robust to the crowd effect compared to the other participants. Additional results are discussed in light of existing and gaps in the literature on the home advantage phenomenon. Alongside the theoretical contribution, these findings contribute to managerial and marketing aspects of sports. Hence, intervention programs and decision are discussed concerning fan behavior and their motivation to attend arenas and stadiums in contrast to alternatives, such as watching the game on TV or on other interactive platforms.